Efficacy and safety of sofosbuvir-based pangenotypic direct-acting antiviral agents for chronic hepatitis C patients without genotype determination: Real-world experience of a retrospective study. Issue 43 (23rd October 2020) - Li, Juan; Wu, Dong-Bo; Jiang, Wei; Chen, Xue-Bin; Xiao, Gui-Bao; Wang, Yong-Hong; Wang, Meng-Lan; Tao, Ya-Chao; Chen, En-Qiang
Abstract : Abstract: Several new, pangenotypic direct-acting antiviral agents (DAAs) have been approved, may reduce the need for genotyping to guide therapy decisions for patients with chronic hepatitis C (CHC). This study aimed to investigate the efficacy and safety of Sofosbuvir (SOF)-based pangenotypic DAAs therapy for CHC patients without genotype (GT determination in the real-world practice. This retrospective cohort study included treatment-naïve CHC patients without GT determination, who received SOF-based DAAs therapy, including 400 mg SOF plus 60 mg daclatasvir (DCV) daily or 400 mg SOF plus 100 mg velpatasvir (VEL) daily for 12 or 24 weeks. Clinical and laboratory data, including sustained virologic response (SVR), were obtained at baseline, end of treatment (EOT), 12 weeks after EOT, and 48 weeks after EOT. A total of 95 CHC patients, including 30 (31.58%) had liver cirrhosis were enrolled. SVR rates after 12 weeks of treatment (SVR12) was 96.84% (92/95), including 96.20% (76/79) of patients receiving SOF plus DCV and 100% (16/16) of patients receiving SOF plus VEL. For 92 patients achieving an SVR12, no virological relapse was observed at 48 weeks after EOT. Furthermore, serum evaluation of liver fibrosis aspartate aminotransferase-to-platelet ratio index and Fibrosis-4 score were decreased significantly at EOT and 12 weeks after EOT, compared to pre-treatment values (both P < .05). Treatment was well-tolerated by our patients. SOF-based pangenotypic DAAs including SOF plus DCV and SOF plus VEL, were effective and safe for CHC patients without GT determination in this study. This may provide a potential simple strategy for CHC treatment without GT determination.